Looking beyond national differences: Cultural consensus between Confucian and Anglo societies. Issue 3 (August 2019) - Venaik, Sunil; Brewer, Paul
National cultural research in management primarily examines cultural differences between countries. Theory and practice recommendations relating to the conduct of international business are then commonly derived from these cultural differences. We propose that attention should also be paid to the ways in which nations are culturally similar . Applying data from the GLOBE national culture model, we reveal cultural similarities across two cultural groups that are usually considered to be representative of important cultural differences. We show six Confucian societies are remarkably similar to seven Anglo societies in respect to their GLOBE culture dimensions scores. We offer support for a so far largely ignored "universal culture" approach in international management that recognizes cultural similarities and balances it with the predominant cultural differences perspective. Implications for management theory and practice are drawn. JEL Classification:M14, M16